Divorce Mediation at Panyabungan Religious Court: Transforming the Desire for Divorce into Reconciliation through Cultural Values in Contemporary Islamic Jurisprudence - Sebyar, Muhamad Hasan; Jafar, Wahyu Abdul; Harahap, Sumper Mulia; Putra, Dedisyah; Efendi, Rahmad (Al-Manahij: Jurnal Kajian Hukum Islam, 2025)
Divorce mediation has emerged as a practical approach to resolving marital disputes, transforming the desire for divorce into an opportunity for reconciliation within contemporary Islamic jurisprudence and cultural contexts. This process highlights the growing importance of integrating cultural values into legal dispute-resolution mechanisms, particularly in Muslim societies where local traditions significantly influence family dynamics. This article assesses the effectiveness of divorce mediation in Indonesia, focusing on its role in reducing conflict, fostering post-divorce cooperation, and supporting the psychological well-being of couples involved. A mixed-methods approach combines quantitative surveys of 111 couples who participated in mediation with in-depth interviews with three professional mediators. Reconciliation was evaluated based on participants' perceptions of post-divorce interactions, particularly their communication and co-parenting abilities. The study acknowledges limitations, such as purposive sampling, which restricts generalizability, and reliance on self-reported data that may introduce bias. Results show that 75% of couples experienced reduced conflict, 95% were satisfied with the outcomes, and 60% reported continued cooperation three years post-divorce. The study emphasizes the role of mediators, structured negotiation processes, and cultural values in successful mediation, recommending improved mediator training and culturally sensitive approaches.